2001
DOI: 10.1021/ol0102388
|View full text |Cite
|
Sign up to set email alerts
|

Three-Component Coupling via the Squarate Ester Cascade as a Concise Route to the Bioactive Triquinane Sesquiterpene Hypnophilin

Abstract: [reaction: see text] A squarate ester cascade is used to provide in one step, via the coupling of three reactants, a highly oxygenated linear triquinane product. The latter is transformed in nine steps into hypnophilin. The access route involves a combination of chlorination, reduction, dehydration, and oxidation maneuvers in the proper sequence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…In 2002, Geng and co-workers presented a direct 10-step route from a squarate ester to hypnophilin ( 8 ) [ 70 ]. The access route involved a combination of chlorination, reduction, dehydration, and oxidation maneuvers in the proper sequence ( Scheme 20 ).…”
Section: Chemical Synthesismentioning
confidence: 99%
“…In 2002, Geng and co-workers presented a direct 10-step route from a squarate ester to hypnophilin ( 8 ) [ 70 ]. The access route involved a combination of chlorination, reduction, dehydration, and oxidation maneuvers in the proper sequence ( Scheme 20 ).…”
Section: Chemical Synthesismentioning
confidence: 99%
“…192 They subsequently found that remote stereoinduction could be achieved through the use of multiple chelating heteroatoms; 193 This methodology has also been utilized in the synthesis of several natural products including hypnophilin, coriolin, and ceratopicanol. 194,195…”
Section: Thermal Reactions 4p Electrocyclizations ( P 4 a )mentioning
confidence: 99%
“…194 The sesquiterpenes hypnophilin, coriolin and ceratopicanol have been synthesised as their racemates. 195,196 Another synthesis of (±)-ceratopicanol has been described by Japanese authors. 197 The total synthesis of the putative structure of isocapnellenone has been reported.…”
Section: Carotane Prezizaane Zizaane and Anisatin Groupmentioning
confidence: 99%